Peningkatan Kapasitas Masyarakat Wala Kabupaten Sidrap dalam Inovasi Biopolimer Lokal “Kakatansea” Untuk Ekonomi Berkelanjutan - Nur Umriani Permatasari; Nur Haedar; Paulina Taba; Djabal Nur Basir; Bulkis Musa; Prayiska Mariana Rapi; Nur Afni; Emmi Astuti; Novi Lestari; Nurmala Sari (JURNAL PENGABDIAN PAPUA, 2025)
The community service program "Enhancing the Capacity of the Wala Community in Sidrap Regency through the Local Biopolymer Innovation 'Kakatansea' for Sustainable Economy" aims to evaluate the effectiveness of interventions in improving community capacity. The main activities include providing education on the utilization of seaweed as an environmentally friendly biopolymer raw material for food and non-food products; training in producing edible coating spray from seaweed polysaccharides to extend the shelf life of local products; training in making modified tempeh from peanuts and seaweed to improve nutrition and shelf life; and training in making environmentally friendly soap with seaweed extract for skin health and economic value. The program involved 50 participants, using a quantitative approach with paired t-test analysis on pre- and post-intervention questionnaire data, measuring understanding, knowledge, and skills through ten key indicators. The results showed a significant increase in the average participant capacity score from 21.06 (pre) to 21.82 (post), with a statistically significant difference (p=0.000; t=-3.882; df=49). This indicates the program’s success in increasing understanding of biopolymers, production processes, product benefits, successful practices, and independent skills. Although the pre- and post-intervention correlation was not significant (r=0.240; p=0.093), the overall increase confirms a positive impact. In conclusion, this program was effective in enhancing the capacity of the Wala community in biopolymer innovation, laying a foundation for sustainable economic development.